Role of brassinosteroids in the adaptation of plant mitochondria functioning in vivo under abiotic stress conditions - Derevyanchuk, M. V.; Grabelnyh, O. I.; Litvinovskaуа, R.P.; Voinikov, V. K.; Sauchuk, A. L.; Khripach, V. A.; Kravets, V. S. (Reports of the National Academy of Sciences of Ukraine, 2015)
The role of brassinosteroids (BRs) in the activation of the mitochondrial electron transport chain under salt stress conditions is investigated. Lowering the endogenous BRs level with the inhibitor of hormone biosynthesis, brassinazole, decreases the cell respiration. We have demonstrated that BRs activate cell respiration and key cellular enzymatic antioxidant systems (catalase, guaiacol peroxidase, superoxide dismutase) and promote the accumulation of osmoprotectors and scavengers of reactive oxygen species (ROS) – glutathione and proline. Our results indicate that BRs may be involved in the regulation of ROS metabolism and mitochondria homeostasis under the abiotic stress condition.